Improvement Of Student Kinesthetic Intelligence - Anggraini, Dwi; Tarmizi, Pebrian; Hasnawati (Perspektif Ilmu Pendidikan, 2023)
This study aims to improve the kinesthetic intelligence of students of the PGSD FKIP University of Bengkulu study program through learning the Basic Concepts of Dance. The research method used is action research conducted in 2 cycles. The research subjects were 38 students of the VC semester. The data collection technique used was observation with a scale of 1-4 for 19 indicators of kinesthetic intelligence and processed by the percentage technique. Based on the results of the study, students' kinesthetic intelligence increased in each cycle. Indicators in categories 1 (poor) and 2 (adequate) decreased in each cycle and indicators in categories 3 (good) and 4 (very good) increased in each cycle. Students are enthusiastic about participating in the lecture process. Kinesthetic intelligence can increase because the exercise is carried out continuously and directed.